A general approach to study molecular fragmentation and energy redistribution after an ionizing event. Issue 3 (13th January 2021) - Erdmann, Ewa; Aguirre, Néstor F.; Indrajith, Suvasthika; Chiarinelli, Jacopo; Domaracka, Alicja; Rousseau, Patrick; Huber, Bernd A.; Bolognesi, Paola; Richter, Robert; Avaldi, Lorenzo; Díaz-Tendero, Sergio; Alcamí, Manuel; et al.
Abstract : We propose to combine quantum chemical calculations, statistical mechanical methods, and photoionization and particle collision experiments to unravel the redistribution of internal energy of the furan cation and its dissociation pathways. Abstract : We propose to combine quantum chemical calculations, statistical mechanical methods, and photoionization and particle collision experiments to unravel the redistribution of internal energy of the furan cation and its dissociation pathways. This approach successfully reproduces the relative intensity of the different fragments as a function of the internal energy of the system in photoelectron–photoion coincidence experiments and the different mass spectra obtained when ions ranging from Ar + to Xe 25+ or electrons are used in collision experiments. It provides deep insights into the redistribution of the internal energy in the ionized molecule and its influence on the dissociation pathways and resulting charged fragments. The present pilot study demonstrates the efficiency of a statistical exchange of excitation energy among various degrees of freedom of the molecule and proves that the proposed approach is mature to be extended to more complex systems.